Comparison of biotic and abiotic parameters between a native secondary forest fragment and a Pinus taeda L. reforestation Comparação de parâmetros bióticos e abióticos entre fragmento de floresta secundária nativa e um reflorestamento de Pinus taeda L. - Talita Parpinelli Ferracin; Valéria Teodoro da Silva; Paulo Souza Medri; Edmilson Bianchini; Jose Antonio Pimenta; Jose Marcelo Domingues Torezan (Semina: Ciências Biológicas e da Saúde, 2010)
The substitution of natural forests for commercial forest plantations can be as damaging as farming or urban occupation. However, studies on natural regeneration in these areas show results in the development of native species in the understory, suggesting a successional process in favor of restoring biodiversity as well as an alternative forrestoration. This work aimed at comparing biotic and abiotic parameters between native secondary forest fragments and Pinus taeda reforestation. The study sites are located at Klabin Ecological Park, Monte Alegre Farm, Telêmaco Borba, Paraná. The following biotic data were evaluated: total height, diameter at breast height (DBH - 1.30 m above the ground) and basal area (BA), in tree species with DBH ≥ 2.5 cm. The following abiotic data were also evaluated: pH, soil compaction, herb cover, canopy cover, litter thickness, air temperature, and relative humidity. Most parameters differed between pine reforestation and secondary forest, such as pH and soil compaction, canopy cover, herb presence and the size structure of vegetation (diameter and height). It was also observed a low regeneration in reforestation, evidenced by the difference in the basal area. However, there was regeneration in pine reforestation, suggesting that, over time, there will be an increase in the regeneration of the native vegetation, increasing the wealth of species and the structural complexity of the vegetation. A substituição das florestas naturais por plantios florestais comerciais, pode ser tão prejudicial quanto a agricultura ou a ocupação urbana. Porém, estudos sobre regeneração natural nessas áreas, apresentam resultados no desenvolvimento de espécies nativas no sub-bosque, sugerindo um processo sucessional favorável à recuperação da biodiversidade e também uma alternativa para a restauração. Este estudo teve como objetivo comparar parâmetros bióticos e abióticos entre fragmento de floresta secundária nativa e reflorestamento com Pinus taeda. O trabalho foi realizado no Parque Ecológico da Klabin, Fazenda Monte Alegre, Telêmaco Borba, Paraná. Foram avaliados dados bióticos (altura total, diâmetro à altura do peito (DAP - 1,30 m do solo) e área basal (AB), das espécies arbóreas com DAP ≥ 2,5 cm) e dados abióticos ( pH e compactação do solo, cobertura de herbáceas, cobertura de dossel, espessura da serapilheira, temperatura e umidade relativa do ar). A maioria dos parâmetros diferiu entre o reflorestamento de pinus e a floresta secundária, como pH e compactação do solo, cobertura do dossel, presença de herbáceas e também a estrutura de tamanho da vegetação (diâmetro e altura). Observou-se também, uma baixa regeneração no reflorestamento, evidenciada pela diferença na área basal. No entanto, houve regeneração no reflorestamento de pinus, e isso sugere que, com o tempo, poderá haver um incremento na regeneração da vegetação nativa, aumentando a riqueza de espécies e a complexidade estrutural da vegetação.